PENGARUH TEKHNIK MENYUSUI YANG BENAR PADA IBU NIFAS TERHADAP KEBERHASILAN PROSES MENYUSUI DI RSI. IBNU SINA BUKITTINGGI - -, Febriniwati Rifdi (Menara Ilmu, 2018)
Background: The exclusive breastfeeding behavior of nowadays has not reach people'sexpectation. The national rate of exclusive breastfeeding is targeted at 95 %. The result ofBasic Health Research Data (Riskesdas) in 2014 states that there are 67.5% mothers who failedto do exclusive breastfeeding the have less knowledge, less confidence that their breast milk issufficient for infant, the mothers are sick, lack of support from husband in breastfeedingprocess and also the infans difficulty of sucking to and nipple confusion, The lack healthworkers in socialization regarding the proper breastfeeding technique can increase thebreastfeeding process based on statistical examination.Sampel: The method used is Quasy experiment research with pre and post test one groupdesign as the type of research. The samples are 23 primiparas, vaginal labour, teknik accidentalsampling.Result : The ability of mothers to do breastfeeding before intervention mean= 2.3±SD=0.765and after intervension mean 8.91±SD=0.288. T-Test examination has been conducted, itindicates that there is an effect of pretest and posttest value of proper breastfeeding techniqueon breastfeeding process with P value = 0,000 which means that there is an effect of properbreastfeeding technique of postpartum mothers on the success of breastfeeding process.Conclution : intervension It is suggested for the future researcher to increase the performanceand competence especially for primipara mothers about the proper breastfeeding technique onthe success of breastfeeding process.